Resisting Anthropomorphism: Evaluation of Abū Sulaymān Al-Khaṭṭābī's (D. 388/998) Approach to Ṣifāt Traditions. (6th April 2022) - Muhammad Noor, Umar; Abur Hamdi, Usman
Abstract: How ṣifāt traditions (hadiths with explicit anthropomorphic content) should be construed remains contentious in the history of Islamic theology. Contrary to most other Islamic scholars, the Hanbalites and modern Salafis prohibit all forms of interpretation, especially ta'wīl (figurative reading). In their perspective, ta'wīl reflects rationalistic epistemology that prefers reason to revelation. They claimed that all hadith authorities held a negative perception of ta'wīl until Ash'arī theologians altered their opinion in the 4th/10 th century. This article argues that ta'wīl acceptance made by hadith scholars was not caused by the theologian's rationalistic influence. Instead, it was a response to ahl al-ḥadīṭh's radical anti-rationalism, which amounted to anthropomorphism. Through examining the thought of Abū Sulaymān al-Khaṭṭābī (d. 388/998), a prominent scholar of hadith in the 4/10 century in dealing with ṣifāt traditions, this study demonstrates how ta'wīl played a vital role in a reform effort that aimed at eliminating the anthropomorphism tendency within traditionists and aṣḥāb al-ḥadīth in 4/10 century.